Trends in Achieving Teaching-Research Connections – From global perspectives to an institutional strategy - Santhanam, Elizabeth (Journal of University Teaching and Learning Practice, 2010)
Research into, and discussions on, the relationships between teaching and research activities in universities and other tertiary education institutions have been gathering momentum for a number of decades in many parts of the world. The foci of these researches and discussions have varied greatly. At one end of the spectrum are the publications which were the result of large-scale projects, generally commissioned by a national body or an institution; these projects often had a broad focus. At the other end are the products of pursuits by an individual with a personal interest in the field, exploring a specific aspect of practice. This paper initially explores some key publications based on commissioned projects in the US, UK and Australia in order to gain a ‘big picture’ view of the teaching-research (TR) connection, then looks at TR relevant discussions emanating from the work of prominent scholars, and finally provides an insight into strategic initiatives for promoting TR connections at an institutional level. The paper provides evidence for the widening of discussion base for TR connections, while narrowing the discussion focus to student engagement, in different parts of the world.